2017
DOI: 10.30537/sijmb.v4i2.109
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Remuneration and Training and Development on Organizational Commitment

Abstract: This study objects to explore the effect of remuneration and training and development (T&D) on organizational commitment (OC). The emphasis of the current study was to clarify a university through remuneration and T&D can accomplish to retain and to be committed with their academic staff. The current study also highlights that remuneration and T&D are best practices which can be adopted and applied even after changes in environment, practices and technology. The study used a cross-sectional and qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(34 reference statements)
1
1
0
Order By: Relevance
“…The results of the study indicated that remuneration positively and significantly affect the employee commitment. The findings of the study are in line with the prior studies (such as Ahmad, Shah, Bibi, & Shah, 2017;Calvin, 2017;Nor, Mohamed, Mohamed, & Hassan, 2020) providing that employees' remuneration is positively related to their commitment in the workplace. The findings further reveal that employees receiving adequate remuneration would behave positively that facilitate the organization in achieving the organizational objectives and competitive advantages.…”
Section: Discussionsupporting
confidence: 89%
“…The results of the study indicated that remuneration positively and significantly affect the employee commitment. The findings of the study are in line with the prior studies (such as Ahmad, Shah, Bibi, & Shah, 2017;Calvin, 2017;Nor, Mohamed, Mohamed, & Hassan, 2020) providing that employees' remuneration is positively related to their commitment in the workplace. The findings further reveal that employees receiving adequate remuneration would behave positively that facilitate the organization in achieving the organizational objectives and competitive advantages.…”
Section: Discussionsupporting
confidence: 89%
“…Such advancement in administrative staff work is emphasised by a subsequent move for a university's administration to be determined as its right (Conway, 2000). Furthermore, the administrative staff's discretionary performance is greatly ignored while the overall performance of the administrative staff is measured (Ahmad et al, 2017;Khurram Shahzad et al, 2016). These mistakes, due to the inattention in the performance of the management system, eventually have a negative effect on the administrative staff's performance.…”
Section: Administrative Staff Performance Is a Major Challenge For Pa...mentioning
confidence: 99%